2017
DOI: 10.1089/aid.2015.0375
|View full text |Cite
|
Sign up to set email alerts
|

CD155 on HIV-Infected Cells Is Not Modulated by HIV-1 Vpu and Nef but Synergizes with NKG2D Ligands to Trigger NK Cell Lysis of Autologous Primary HIV-Infected Cells

Abstract: Activation of primary CD4+ T cells induces the CD155, but not the CD112 ligands for the natural killer (NK) cell activation receptor (aNKR) CD226 [DNAX accessory molecule-1 (DNAM-1)]. We hypothesize that HIV productively infects activated CD4+ T cells and makes itself vulnerable to NK cell-mediated lysis when CD155 on infected T cells engages DNAM-1. The primary objective of this study is to determine whether CD155 alone or together with NKG2D ligands triggers autologous NK cell lysis of HIV-infected T cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…The lack of a benefit for TIGIT blockade may also be explained by the fact that TIGIT is simply not engaged during NK cell recognition of HIV-infected cells. We found that TIGIT ligands CD155 and CD112 are not upregulated on CD4 + T cells by HIV infection in vitro, consistent with previous reports [67][68][69]. We also found that TIGIT ligands were not upregulated in HIV + women, though this differs from the findings of Yin et al [48], who reported elevated CD155 expression on CD4 + T cells from HIV-infected individuals.…”
Section: Nk Cells Undergo Significant Changes During Chronic Hiv Infesupporting
confidence: 91%
“…The lack of a benefit for TIGIT blockade may also be explained by the fact that TIGIT is simply not engaged during NK cell recognition of HIV-infected cells. We found that TIGIT ligands CD155 and CD112 are not upregulated on CD4 + T cells by HIV infection in vitro, consistent with previous reports [67][68][69]. We also found that TIGIT ligands were not upregulated in HIV + women, though this differs from the findings of Yin et al [48], who reported elevated CD155 expression on CD4 + T cells from HIV-infected individuals.…”
Section: Nk Cells Undergo Significant Changes During Chronic Hiv Infesupporting
confidence: 91%
“…We analyzed by flow cytometry the expression of some ligands on target cells that either trigger NK activation or initiate inhibitory NK signaling by binding to NK inhibitory receptors. The activating ligands included NTB-A, which binds NTB-A on the NK cell surface and leads to activation and secretion of interferon-γ, CD48, which binds 2B4, ULBP-1 and -2, ligands that bind NKG2D and that have been demonstrated to be upregulated in the setting of HIV-1 infection by the viral protein vpr ( 32 ), and CD155, a NK ligand that binds DNAM-1 on NK cells and induces activation ( 33 ). The inhibitory included HLA-E and HLA-Bw4, NK ligands that initiate inhibitory NK signaling by binding to NK receptors NKG2A and KIR3DL1, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, reports on HIV-mediated regulation of the expression of other NKG2D ligands, i.e., MIC-A and MIC-B, on CD4 + T cells are conflicting [ 52 , 54 , 55 ]. HIV infection induces the loss of surface expression of CD155 on the Jurkat T cell line, however, this could not be reproduced in bulk p24 + primary HIV NL4-3 -infected T cells, which found CD155 to be modestly upregulated [ 56 , 57 , 58 ]. Infection of the human monocytic cell line U937 with primary isolates of an Indian HIV-1 subtype C induced the downregulation of CD80 and CD86 [ 59 ].…”
Section: Discussionmentioning
confidence: 99%